Formation of 4-keto-D-aldopentoses and 4-pentulosonates (4-keto-D-pentonates) with unidentified membrane-bound enzymes from acetic acid bacteria - Adachi, Osao (2011)
In our previous study, a new microbial reaction yielding 4-keto-D-arabonate from 2,5-diketo-D-gluconate was identified with Gluconacetobacter liquefaciens RCTMR 10. It appeared that decarboxylation and dehydrogenation took place together in the reaction. To analyze the nature of the reaction, investigations were done with the membrane fraction of the organism, and 4-keto-D-arabinose was confirmed as the direct precursor of 4-keto-D-arabonate. Two novel membrane-bound enzymes, 2,5-diketo-D-gluconate decarboxylase and 4-keto-D-aldopentose 1-dehydrogenase, were involved in the reaction. Alternatively, D-arabonate was oxidized to 4-keto-D-arabonate by another membrane-bound enzyme, D-arabonate 4-dehydrogenase. More directly, D-arabinose oxidation was examined with growing cells and with the membrane fraction of G. suboxydans IFO 12528. 4-Keto-D-arabinose, the same intermediate as that from 2,5-diketo-D-gluconate, was detected, and it was oxidized to 4-keto-D-arabonate. Likewise, D-ribose was oxidized to 4-keto-D-ribose and then it was oxidized to 4-keto-D-ribonate. In addition to 4-keto-D-aldopentose 1-dehydrogenase, the presence of a novel membranebound enzyme, D-aldopentose 4-dehydrogenase, was confirmed in the membrane fraction. The formation of 4-keto-D-aldopentoses and 4-keto-D-pentonates (4-pentulosonates) was finally confirmed as reaction products of four different novel membrane-bound enzymes.